NEWSPAPER "KOMPAS" IN INDONESIAN POLITICAL CONSTELLATION (1960-1980) - Krissandi, Apri Damai Sagita (International Journal of Humanity Studies (IJHS), 2018)
This study aims to describe the situation experienced by Kompas newspaper in the context of Indonesian politics from 1960 to 1980. This method of this research is a qualitative descriptive study describing an event with a historical approach. The method used is critical discourse analysis by reviewing the editorial from Kompas newspaper from 1960 to 1980. From the research result, it was found that Malari incident (fifteenth of January 1974) was the starting point of Kompas during the New Order era. Kompas is considered an idealist newspaper, Kompas which expresses people's conscience and aspirations, boldly and critically exercises  social control. The pre-Malari Kompas is a free, independent and articulate newspaper. On the contrary, post-Malari Kompas is a less idealist newspaper, which tends to represent the interests of the rulers, government or even the state which never exercise social control critically, decisively, and courageously. The post-Malari Kompas is a newspaper that is not free or at least a newspaper that has a very limited independence. DOI: https://doi.org/10.24071/ijhs.2018.010207